Strategi Penilaian Formatif melalui Lingkungan Belajar Virtual (LBV) - Hamzah Robbani; Windi Megayanti; Alloysius Vendhi Prasmoro (NUCLEUS, 2020)
The purpose of this study is to provide easy use of elearning / LBV (virtual learning environment) for educational units in providing formative assessments to students using online learning methods. This research method uses a research and development approach with a qualitative approach. tutors find it more easier to use different templates on the LBV than have been used. This research results in the importance of selecting a User friendly LBV template for LBV, especially for formative assessments